Could Executive Compensation Incentive Enhance the Efficiency of Enterprise Resource Allocation? An Empirical Study from China - Xianan Yin; Hua Ming; Jing Cui; Xinzhong Bao (Discrete Dynamics in Nature and Society)
Corporate executives have the decision-making power of resource allocation, and efficient resource allocation is an important measure of high-quality development of enterprises. It is a focal issue whether the compensation incentive can promote the executives to make better use of the enterprise resource allocation. We investigate this question using the data of the Chinese listed companies in 2015–2019 based on Data Envelopment Analysis (DEA) and fixed effect model. The results show the following: (1) both monetary compensation incentive and equity incentive can significantly improve the efficiency of resource allocation, and the former is more significant; (2) there is an inverted U-shaped relationship between perquisite consumption incentive and resource allocation efficiency; (3) the above conclusion is still true in state-owned enterprises; (4) in private enterprises, the effect of equity incentive is more effective, but the effect of perquisite consumption incentive is less significant. The results highlight the relationship between compensation incentive and enterprise resource allocation. Our study is expected to guide the executives to formulate reasonable compensation incentives and improve the efficiency of resource allocation.